2020
DOI: 10.20944/preprints202001.0062.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Analysis of Membrane Targeting by the C2 Domain of the E3 Ubiquitin Ligase Smurf1

Abstract: SMAD ubiquitination regulatory factor 1 (Smurf1) is a Nedd4 family E3 ubiquitin ligase that regulates cell motility, polarity and TGFβ signaling. Smurf1 contains an N-terminal protein kinase C conserved 2 (C2) domain that targets cell membranes and is required for interactions with membrane-localized substrates such as RhoA. Here we investigated the lipid-binding mechanism of Smurf1 C2, revealing a general affinity for anionic membranes in addition to a selective affinity for phosphoinositides (PIPs).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Smurf2-C2 shares 87% sequence identity with the C2 domain of Smurf1 (Figure S5), and they have similar functions and structure (Koganti et al, 2018), which make it relevant to compare them. Scott et al (2020) used MD simulations to explore interactions of InsPs with Smurf1-C2 and observed a canonical top binding mode, in line with our results. Moreover, Smurf1-C2 has been crystallized with negatively charged sulfates bound, also on the top of the C2 domain (PDB: 3PYC; Figure S5).…”
Section: Smurf2supporting
confidence: 76%
See 1 more Smart Citation
“…Smurf2-C2 shares 87% sequence identity with the C2 domain of Smurf1 (Figure S5), and they have similar functions and structure (Koganti et al, 2018), which make it relevant to compare them. Scott et al (2020) used MD simulations to explore interactions of InsPs with Smurf1-C2 and observed a canonical top binding mode, in line with our results. Moreover, Smurf1-C2 has been crystallized with negatively charged sulfates bound, also on the top of the C2 domain (PDB: 3PYC; Figure S5).…”
Section: Smurf2supporting
confidence: 76%
“…There have been a number of MD studies of the interaction of Ca 2+ -dependent C2 domains with membranes, revealing how Ca 2+ ions mediate interactions between the protein and anionic lipids such as phosphatidylserine (PS) and phosphatidylinositol phosphates (PIPs) ( Alwarawrah and Wereszczynski, 2017 ; Banci et al., 2002 ; Chon et al., 2015 ; Jaud et al., 2007 ; Lai et al., 2010 ; Manna et al., 2008 ; Michaeli et al., 2017 ; Vermaas and Tajkhorshid, 2017 ). However, there have not been many simulation studies of the interactions of Ca 2+ -independent C2 domains with membranes (see, e.g., Alnaas et al., 2021 ; Scott et al., 2020 ) other than for PTEN ( Shenoy et al., 2012a ; Treece et al., 2020 ), despite the growing recognition of the importance of such interactions in a number of cellular processes ( Stahelin et al., 2014 ). Here, we use coarse-grained molecular dynamics (CG-MD) ( Ingólfsson et al., 2014 ; Marrink and Tieleman, 2013 ) to examine and compare the interactions of six different Ca 2+ -independent C2 domains with lipid bilayers: C2 domains from KIBRA (PDB: 6FJD ), PI3KC2α (PDB: 6BU0 ), RIM2 (PDB: 2BWQ ), PTEN (PDB: 1D5R ), Smurf2 (PDB: 2JQZ ), and SHIP2 (PDB: 5OKM ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the essential roles of protein containing the C2 domain in endocytosis, cellular metabolism and cancer 29 - 31 . TC2N expression is also associated with the prognosis and development of human lung cancer and breast cancer 16 - 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the essential roles of protein containing the C2 domain in endocytosis, cellular metabolism and cancer [29][30][31]. TC2N expression is also associated with the prognosis and development of human lung cancer and breast cancer [16][17][18].…”
Section: Discussionmentioning
confidence: 99%